2009
DOI: 10.1111/j.1600-079x.2009.00727.x
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antitumor effect of melatonin with several chemotherapeutic drugs on human Ewing sarcoma cancer cells: potentiation of the extrinsic apoptotic pathway

Abstract: Ewing sarcoma, the second most frequent bone cancer type, affects mainly adolescents, who have a survival of 50% 5 yr after diagnosis. Current treatments include a combination of surgery, radiotherapy and chemotherapy, which present potential serious side effects. Melatonin, a natural molecule without relevant side effects, has been previously shown to induce cytotoxicity in SK-N-MC cells, a Ewing sarcoma cell line. Here, we found that there is a synergy in the antitumor effect when melatonin (50 mum-1 mm) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
129
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(136 citation statements)
references
References 47 publications
(52 reference statements)
7
129
0
Order By: Relevance
“…In line with this notion are the findings that microtubule-destabilizing agents, such as VAs, cause the activation of caspase-3 (Fan et al, 2001), and silencing of DCLK leads to the activation of caspase-3 as well (Verissimo et al, 2010). Previous studies have shown that VAs induce caspase-8 activation (Bayless and Davis, 2004;Casado-Zapico et al, 2010). We have detected an increase in caspase-8 activity in NB cells treated with the combination of VAs and DCLK knockdown compared with cells treated with VAs alone.…”
Section: Discussionsupporting
confidence: 52%
“…In line with this notion are the findings that microtubule-destabilizing agents, such as VAs, cause the activation of caspase-3 (Fan et al, 2001), and silencing of DCLK leads to the activation of caspase-3 as well (Verissimo et al, 2010). Previous studies have shown that VAs induce caspase-8 activation (Bayless and Davis, 2004;Casado-Zapico et al, 2010). We have detected an increase in caspase-8 activity in NB cells treated with the combination of VAs and DCLK knockdown compared with cells treated with VAs alone.…”
Section: Discussionsupporting
confidence: 52%
“…Furthermore, melatonin acts to prevent many of the H 2 O 2 -induced alterations in the MAPK and mTOR signaling pathways in H4IIE hepatoma cells [15]. Melatonin down-regulates Akt leading to TGFβ-1-dependent growth inhibition of breast cancer cells [16,17]. Yet the exact roles of melatonin on autophagic pathway in the process of cancer progression still need to be further elucidated.…”
Section: Introductionmentioning
confidence: 97%
“…At both physiological and pharmacological concentrations, melatonin acts as a differentiating agent in some cancer cells and lowers their invasive and metastatic status through alterations in adhesion molecules and maintenance of gap junctional intercellular communication. In other cancer cell types, melatonin, either alone or in combination with other agents, induces apoptotic cell death (Blask et al, 2002;Casado et al, 2010;Rodringuez-Garcia et al, 2012). Melatonin reduces tumor growth in experimental models in vivo and proliferation and invasive properties of cancer cells in culture (Cos et al, 2002;Manda and Bhatia, 2003).…”
Section: Discussionmentioning
confidence: 99%